2023
DOI: 10.2514/1.c037027
|View full text |Cite
|
Sign up to set email alerts
|

Level-Set Mass-Conservative Front-Tracking Technique for Multistep Simulations of In-Flight Ice Accretion

Abstract: This paper presents a novel level-set-based approach to model evolving boundary problems for in-flight ice accretion. No partial differential equations are solved as in the standard level-set formulation, but simple geometrical quantities are employed to provide an implicit discretization of the updated boundary. This method avoids mesh entanglements and grid intersections typical of algebraic and mesh deforming techniques, making it suitable for generating a body-fitted discretization of arbitrarily complex g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In fact, this process must be robust and automated so that no user intervention is required throughout the process. Following the work proposed in [14], the new ice-air interface is represented as the zero-contour level of a level-set function [33]. Given a 2D, or 3D, domain Ω ⊂ R 2,3 , a curve, or a surface, can be represented by a certain level-set (or isocontour) of the auxiliary function 𝜙(x), with x ∈ Ω.…”
Section: Geometry Updating Modulementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, this process must be robust and automated so that no user intervention is required throughout the process. Following the work proposed in [14], the new ice-air interface is represented as the zero-contour level of a level-set function [33]. Given a 2D, or 3D, domain Ω ⊂ R 2,3 , a curve, or a surface, can be represented by a certain level-set (or isocontour) of the auxiliary function 𝜙(x), with x ∈ Ω.…”
Section: Geometry Updating Modulementioning
confidence: 99%
“…In [14], the discrete level-set field was built considering the ice thickness to be accreted at the airfoil boundary and the distance of each grid node from it. This work defines the level-set scalar field with a novel algorithm, which can accurately describe the new ice-air interface even for large displacements.…”
Section: Geometry Updating Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Ice accretion is a complex multi-physics problem. Numerical modelling of the problem requires, in general, four steps: (1) the computation of the flow field around the geometry under analysis; in our framework, SU2 is used; (2) the computation of the trajectory of the droplets, to assess the fraction of free-stream water mass collected at a given location over the object's surface, i.e., the collection efficiency β = dA i dA∞ ; we use the in-house developed code PoliDrop [16]; (3) the computation of the ice growth with a thermodynamic module (PoliMIce [17]); and (4), the update and re-meshing of the geometry to restart from step (1), both for 2D and 3D geometries [18]. Indeed, accurate numerical representation of the evolution of the ice shape on a wing requires frequent updates of the geometry using a multi-step approach.…”
Section: Ice Accretion Frameworkmentioning
confidence: 99%
“…Indeed, accurate numerical representation of the evolution of the ice shape on a wing requires frequent updates of the geometry using a multi-step approach. Donizetti et al [19] recently showed that there is a strict relationship between the local ice thickness, the surface discretization, and the update frequency, allowing also to automatically set a timevarying optimal time discretization in the multi-step process.…”
Section: Ice Accretion Frameworkmentioning
confidence: 99%